The influence of meta-cognitive listening strategies on listening performance in the MALL: the mediation effect of learning style and self-efficacy - Shaojie, Tan; Abd Samad, Arshad; Ismail, Lilliati (SAGE Publications, 2024)
The ability to understand listening is an essential skill for non-native speakers of English as a foreign language (EFL). Research has shown that several factors can influence EFL students’ English listening comprehension, including the listening strategy they use during listening activities. This study, therefore, used the meta-cognitive listening strategy to explore the mediation role of learning style and self-efficacy in the relationship with listening performance. In this study, 632 Chinese university students participated in a survey and completed electronic questionnaires on MALQ (Meta-cognitive Awareness of Listening Questionnaire), PLSPQ (Perceptual Learning Style Preference Questionnaire), and GSE (General Self-Efficacy Scale). The data were analyzed using AMOS software and a structural equation modeling (SEM) technique. The results showed that students’ listening strategy directly and positively predicted their English listening performance. Moreover, students’ listening performance was fully mediated by learning style and self-efficacy. After discussing these findings, suggestions as well as limitations for future studies will be given. The findings of this study are expected to contribute to a better understanding of the factors that may affect EFL students’ English listening comprehension and inform instructional practices in the EFL classroom. Specifically, the results of this study may suggest the use of teaching strategies tailored to individual learning styles and the adoption of measures to improve self-efficacy of EFL students. Ultimately, the goal of this research is to improve EFL students’ English listening comprehension skills and enhance their overall language proficiency.